Lékar a pocítac. 26. Komercni software - Brezovský, P; Hladíková, M; Kasal, P (Ceskoslovenska pediatrie, 1989)
The authors give an account of different types of commercially supplied programmes which can be used also in the health services. They discuss the properties and types of different software - data base programmes, text processors, graphic and statistical programmes and finally so-called integrated software along with data on possible mutual combinations. At the same time also general conditions for the application of these programmes within the framework of clinical informations systems are discussed incl. their advantages and short-comings.
Keywords: Medical Informatics; lékařská informatika; Software; software